How the impacts of burst water mains are influenced by soil sand content - Farewell, Timothy S.; Jude, Simon; Pritchard, Oliver G. (European Geosciences Union (EGU) / Copernicus Publications, 2018)
Society relies on infrastructure, but as infrastructure systems are often collocated and interdependent, they are vulnerable to cascading failures. This study investigated cross-infrastructure and societal impacts of burst water mains, with the hypothesis that multi-infrastructure failures triggered by burst water mains are more common in sandy soils. When water mains in sandy soils burst, pressurised water can create subsurface voids and abrasive slurries, contributing to further infrastructure failures. Three spatial data investigations, at nested scales, were used to assess the influence that soil sand content has on the frequency and damage caused by burst water mains (1) to roads in the county of Lincolnshire, (2) to other proximal water mains in East Anglia and (3) to other proximal infrastructure and wider society across England and Wales. These investigations used infrastructure network and failure data, media reports and soil maps, and were supported by workshop discussions and structured interviews with infrastructure industry experts. The workshop, interviews and media reports produced a greater depth of information on the infrastructure and societal impacts of cascading failures than the analysis of infrastructure data. Cross-infrastructure impacts were most common on roads, built structures and gas pipes, and they occurred at a higher rate in soils with very high sand contents.